1990
DOI: 10.1044/jshr.3303.476
|View full text |Cite
|
Sign up to set email alerts
|

Acoustic Dimensions of Hearing-Impaired Speakers’ Intelligibility

Abstract: Regression and principal components analyses were employed to study the relationship between 28 segmental and suprasegmental acoustic parameters of speech production and measures of speech intelligibility for 40 severely to profoundly hearing-impaired persons in an effort to extend the findings of Metz, Samar, Schiavetti, Sitler, and Whitehead (1985). The principal components analysis derived six factors that accounted for 59% of the variance in the original 28 parameters. Consistent with the findings of Metz … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

1992
1992
2021
2021

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(22 citation statements)
references
References 23 publications
1
21
0
Order By: Relevance
“…The profoundly hearing impaired adolescent speakers did not distinguish between aspirated and unaspirated initial stops in terms of VOT in that the values of the VOT for both stops were similar to the lower values for unaspirated stops as produced by the control speakers. Such findings are in agreement with the results of acoustic studies on initial stops produced by profoundly hearing impaired speakers who studied in schools for the deaf, both in English (Monsen, 1976;Samar et al, 1989;Metz et al, 1990) and in French (Ryalls, Larouche, & Giroux, 2003). Tam (1996) reported that Cantonese-speaking profoundly hearing impaired children who were integrated into normal schools produced aspirated stops with significantly longer VOT than the unaspirated stops.…”
Section: Production Of Votsupporting
confidence: 84%
“…The profoundly hearing impaired adolescent speakers did not distinguish between aspirated and unaspirated initial stops in terms of VOT in that the values of the VOT for both stops were similar to the lower values for unaspirated stops as produced by the control speakers. Such findings are in agreement with the results of acoustic studies on initial stops produced by profoundly hearing impaired speakers who studied in schools for the deaf, both in English (Monsen, 1976;Samar et al, 1989;Metz et al, 1990) and in French (Ryalls, Larouche, & Giroux, 2003). Tam (1996) reported that Cantonese-speaking profoundly hearing impaired children who were integrated into normal schools produced aspirated stops with significantly longer VOT than the unaspirated stops.…”
Section: Production Of Votsupporting
confidence: 84%
“…Several dysarthria studies have used multiple tasks (i.e., direct magnitude estimation vs. transcription) to index intelligibility for different types of speech stimuli (e.g., Metz, Schiavetti, Samar, & Sitler, 1990;Sussman & Tjaden, 2012;Yunusova, Weismer, Kent, & Rusche, 2005). However, limited knowledge is available about how objective and subjective metrics of intelligibility compare for the same stimuli.…”
Section: Comparison Of Intelligibility Measuresmentioning
confidence: 99%
“…However, this technique has been used in previous studies of intelligibility, even with a smaller-than-optimal ratio of number of subjects to predictor variables (e.g. Monsen, 1978;Ansel, 1985;Metz, Samar, Schiavetti, Sitler and Whitehead, 1985;Metz, Schiavetti, Samar and Sitler, 1990;Whitehill and Ciocca, 2000).…”
Section: Discussionmentioning
confidence: 97%